IMPLEMENTING ENVIRONMENTAL CHARACTER EDUCATION IN AN ISLAMIC SCHOOL WITHIN A MUSLIM MINORITY CONTEXT: A CASE STUDY IN SOUTHERN THAILAND - Izzatul Bariyah; Novera Luthfiani; Novia Suci Safitri; Adinda Yuliana Musthofa; Nada Nabila (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
Environmental character education is vital for strengthening environmental awareness, particularly in Islamic schools within minority contexts. This study examines the implementation of religiously grounded environmental character education at an Islamic school in Southern Thailand, using a qualitative descriptive approach through observation, interviews, documentation, and literature review. Findings show that the school applies a systematic habituation model based on Fathnuryati Hidayah's framework, comprising routine activities, spontaneous actions, and exemplary behavior. Religious values are integrated through the Tarbiyah program, linking cleanliness and environmental responsibility to Islamic principles. Success indicators include near-total student participation in Tarbiyah, improved classroom and schoolyard cleanliness, and greater accuracy in waste sorting. Obstacles identified include uneven student awareness, limited cleaning facilities, and weather-related disruptions to outdoor activities. The study concludes that the school effectively cultivated environmental values through religious teaching, daily habits, and teacher modeling. These findings imply that Islamic schools in similar minority contexts can adopt the Tarbiyah-based habituation model as a practical, low-resource strategy for environmental character education. Integrating Islamic values, such as cleanliness as part of faith and nature as divine trust, into daily routines demonstrates that spiritual frameworks can effectively drive sustainable behavioral change without dependence on formal government programs.